The e-policy handbook designing and implementing effective e-mail, Internet, and software policies - Flynn, Nancy, 1956- (AMACOM, 2001)
This text provides step-by-step guidelines for creating up-to-date, legally sound policies that explicitly define the rights and obligations of employees when using e-mail and the Internet. This handbook covers cyberlaw, e-risk, e-insurance, writing and formatting policies, training, and more.